Regional integration and Brazilian Foreign Policy: Strategies in the South American space - Pecequilo, Cristina Soreanu; Carmo, Corival Alves do (Revista de Sociologia e Política, 2013)
The aim of the article is to present, based on theoretical studies of integration, the evolution of this process in Latin America and, most recently, in South America. Based on these studies, the goal is to analyze the role played by Brazil in the process, which defines as priorities of its foreign policy a regional and global framework for its international action that is based on both cooperation and power projection.The research has been conducted based on theories of integration, an historical background on Latin American integration and in Brazilian foreign policy, through its contemporary agenda. The answer was based on a comparative agenda and in a bibliographical critical analysis of the research material.The main findings of the paper point out that Latin American integration has specific features linked to the economic, political and stragetic realities of the continent that show the limitations of some theories applied to the European process, also that it depends on Brazilian foreign policy actions, that still sees the region as instrumental to its interests. So, Brazil sometimes fail to fulfill some requisites of integration that are essential to sustain its projects. Therefore, there is a cycle of enlargement and deepening of regional integration process in this political space that point out to the need of a more sustained compromise of Brazilian foreign policy towards these projects. If Brazil continues not to sustain these projects, they will lose momentum and significance once more, increasing power asymmetries in the region.